DEVELOPMENT OF TEACHING MATERIALS BASED ON CONTEXTUAL VIDEO TO IMPROVE THE STUDENT HIGHER ORDER THINGKING SKILLS OF ANIMAL PHYSIOLOGY COURSE - Hapsari, Ari Indriana (University of Muhammadiyah Malang, 2016)
he important demands in learning in college is the lecturer should empower the potential of students with various skills primarily related to Higher Order Thinking Skills (HOTS). These aspects need to attention by the lecture, seeing that in the 21st century learning skills, critical thinking, creative, make decisions, and solve problems is required in the work. Through the development based on contextual video teaching materials is expected to increase HOTS students of animal physiology subjects. The method used in this research is the ADDIE (Analysis, Design, Development, Implementation and Evaluation). Results of this study was an increase in the average value HOTS activity after treatment where the value of the average highest and lowest C41 analysis indicators are C52 evaluation indicators. Ngain value calculation is equal to 0.2 with a low category. While the results of the validation of two experts in a row both material and media experts in the amount of 3.2 and 3.12 in both categories.